Integrasi Literasi Digital dalam Pembelajaran Anak Usia Dini: Analisis Sistematis tentang Dampak dan Strategi Implementasi di Era PostPandemic - Awaliana, Satma; Ramadhani, Rahma (Prodi PIAUD STAI AL-GAZALI BONE, 2025)
The COVID-19 pandemic has accelerated digital transformation in various sectors, including earlychildhood education (PAUD), which demands rapid adaptation to the use of technology in learning.This literature research aims to systematically analyze the impact of digital literacy integration inearly childhood and formulate effective implementation strategies in the post-pandemic era. Througha review of 75 selected studies from databases such as Scopus, ERIC, and Google Scholar (2019–2023), this study identified that digital literacy not only improves children's technical skills, but alsohas the potential to optimize cognitive, social, and emotional development when designed with anage-appropriate approach. However, the findings also reveal significant risks, includingoverexposure to screens, reliance on passive content, and technology access gaps that exacerbateeducational inequality. The positive impact of digital literacy can be seen in improving children'scritical thinking skills through game-based interactive applications, such as platforms that combinebasic math elements with creative narratives. Case studies in Finland and Singapore show that theuse of Augmented Reality (AR)-based digital tools is able to stimulate children's interest in exploringthe surrounding environment. On the other hand, research in developing countries such as Indonesiaand Kenya reveals infrastructure challenges, such as limited gadgets, internet connectivity, andinadequate teacher competence. The parental factor is also key: active family participation inaccompanying the use of technology has been shown to reduce the risk of addiction and maximizethe benefits of learning. The practical implications of this study include policy recommendations forthe government in developing an adaptive early childhood education curriculum, such as theintegration of digital literacy modules in teacher training and the standardization of evidence-basededucational content. For parents, it's important to establish a clear